Lower 25-hydroxyvitamin D is associated with long menstrual cycles in a prospective cohort study - Jukic, Anne Marie Z. (Epidemiology, 2018)
BACKGROUND: Vitamin D insufficiency is associated with subfertility and prolonged estrus cycles in animals, but humans have not been well-studied. METHODS: A prospective time-to-pregnancy study, Time to Conceive (2010–2015), collected up to four months of daily diary data. Participants were healthy, late reproductive-aged women in North Carolina who were attempting pregnancy. We examined menstrual cycle length as a continuous variable, as well as in categories: long (35+ days) and short (≤25 days). Follicular phase length and luteal phase length were categorized as long (18+ days) or short (≤10 days). We estimated associations between those lengths and serum 25-hydroxyvitamin D (25(OH)D) using linear mixed models and marginal models. RESULTS: There were 1278 menstrual cycles from 446 women of whom 5% were vitamin D deficient (25(OH)D <20ng/ml), 69% were between 20 and 39ng/ml, and 26% were 40ng/ml or higher. There was a dose-response association between vitamin D levels and cycle length. Compared with the highest 25(OH)D level (≥40ng/ml), 25(OH)D deficiency was associated with almost three times the odds of long cycles (adjusted odds ratio (aOR) (95% confidence interval (CI)): 2.8 (1.0, 7.5)). The aOR was 1.9 (1.1, 3.5) for 20–<30ng/ml. The probability of a long follicular phase and the probability of a short luteal phase both increased with decreasing 25(OH)D. CONCLUSIONS: Lower levels of 25(OH)D are associated with longer follicular phase and an overall longer menstrual cycle. Our results suggest that vitamin D affects the reproductive axis, suggesting broader implications for reproductive success.